Trophic ulcers of the lower extremities in centenarians: are there any features? - Leonid I. Bubman; Svetlana V. Topolyanskaya; Viktor V. Karpov; Stanislav O. Khan; Mariya А. Korshunova; Karine A. Lytkina; Georgii G. Melkonya; Svetlana A. Rachina; Leonid I. Dvoretsky (LLC "MEDIAFORMAT", 2023)
Aim. To compare various clinical and laboratory parameters in centenarians and old patients with trophic ulcers of the lower extremities. Materials and methods. 100 patients were enrolled in the cross-sectional study; 45 centenarians with trophic ulcers - in the main group, 55 patients with trophic ulcers younger than 90 years - in the control group. The age of study patients varied from 61 to 101 years, averaging 82.9±10.5 years. The majority of study patients were women (70%). Results. 40% of ulcers in centenarians were venous ulcers, 24.4% - arterial, 20% - mixed ulcers. Centenarians had a smaller number of ulcers (p=0.03), a shorter duration of ulcers (p=0.01), a smaller area and less infection, compared with patients younger than 90 years. Atrial fibrillation was registered in 46.7% of centenarians, while in patients younger than 90 years this arrhythmia was observed in 31.4% of cases (p=0.02). 22.2% of centenarians and 43.4% of patients under 90 years of age suffered from diabetes mellitus (p=0.001). 11.1% of centenarians and 18.9% of patients of old age suffered stroke in the past (p<0.001). There were no differences in the incidence of myocardial infarction in history (p=0.92) and chronic heart failure (p=0.97) between groups of patients. Among centenarians, 45.2% of patients had normal body weight, 31% were overweight, 23.8% were obese, while in the group of patients younger than 90 years, obesity was registered in 53.7%, and only 22.2 of patients had a normal body mass index (p=0.001). The body mass index in centenarians reached an average of 27.2±6.0 kg/m2, in elderly and senile patients it was 33.7±11.2 (p<0.0001), and the weight was 67.9±16.3 kg and 92.2±33.2 kg, respectively (p<0.0001). The mean count of leukocytes in centenarians was 6.4±2.3×109/l, in patients younger than 90 years - 7.3±2.8×109/l (p=0.07), and platelets - 233±87×109/l and 291±117×109/l, respectively (p=0.006). The mean level of C-reactive protein in centenarians was 12.4±14.7 mg/l, and in patients younger than 90 years it was 26.5±34.0 mg/l (p=0.04). An inverse correlation was observed between the level of C-reactive protein and the age of patients (r=-0.49; p<0.0001). In the group of centenarians a direct correlation was registered between ESR and C-reactive protein level (r=0.49; p=0.02). Conclusions. The study results indicate a number of features of various clinical and laboratory parameters in centenarians with trophic ulcers of the lower extremities, compared with similar old patients.